Effect Of Latihan Pasrah Diri (Lpd) Plus Fluoxetin Compared With Fluoxetin Alone To Improve Fructosamine Level In Tipe 2 Diabetes Mellitus Patients With Depression Symptoms - Natsir Muin; Agus Siswanto; Ahmad Husain Asdie (Acta Interna The Journal of Internal Medicine, 2017)
ABSTRACTBackground. Depression is a risk factor for diabetes and diabetes increase the risk for depression. Depression contributes to progression of diabetes mellitus. Examination of fructosamine is used to monitor blood sugar control for 2-3 weeks (according to age albumin). LPD evoke the relaxation response, which expected to improve symptoms of stress or depression.Objective. To determine the decrease in fructosamine levels in the group of patients with diabetes mellitus with depression symptoms after administration of fluoxetine alone compared with a combination of fluoxetine and LPD.Methods. This research conducted in Dr.Soeradji Tirtonegoro General Hospital, in May to August 2014. Distribution of data tested using the Shapiro-Wilk test. The differences between fructosamine and BDI (Beck Depression Inventory) before and after treatment tested with a pair t-test if normally distributed or Wilcoxon test if it was not normally distributed. The decrease in fructosamine and BDI both groups compared by independent t-test if normally distributed or Mann Whitney U test if not normally distributed. Differences were considered significant if p <0.05 with a confidence interval of 95%.Result. There was a significant decrease in fructosamine levels in treatment group from 293.90±140.042 to 239.01±133.13 after treatment with p value 0.017 (p <0.05). Control group from 263.13±163.65 to 219.01±149.33 with p value 0.001 (p<0.05). The decrease of fructosamine levels not differ in the treatment group 67.24±102.71 than the control group 71.14 ± 72.77 with p value = 0.902 (p> 0.05).Conclusion. LPD had no effect on fructosamine levels of type 2 diabetes mellitus patients with depression symptoms.Keywords: LPD, symptoms of depression, fructosamine, BDI (Beck Depression Inventory)